Piston ring wear and cylinder liner tribofilm in tribotests with lubricants artificially altered with ethanol combustion products. (February 2015) - Lenauer, Claudia; Tomastik, Christian; Wopelka, Thomas; Jech, Martin
Abstract: To investigate the effects of bioethanol on the piston ring–cylinder liner system, tribological tests were carried out on a model tribometer set-up, measuring friction and piston ring wear. The bioethanol influence is accounted for by adding ethanol combustion products during an artificial engine oil alteration process and using these lubricants in the tribotests. Also, a chemical surface analysis of the wear zone on the cylinder liners was carried out. There is a significant difference in the performance of these artificially altered oils in comparison to their fresh counterparts, and different lubricants are affected differently by the alteration process. A close correlation was found between the steady-state wear rate of the piston ring and the tribofilm thickness on the cylinder liner. Highlights: Wear measurement of piston rings using radioactive isotopes in tribometer tests. Surface analysis of cylinder with XPS. Lubrication with engine oils aged under the influence of ethanol combustion products. Lower constant wear rate for aged lubricants. Tribofilm thickness and constant wear rate correlate.